Bizarre behavior during intracarotid sodium amytal testing (Wada test): are they predictable? Reações bizarras durante o teste do amital sódico intracarotídeo (TASI ou Teste de Wada): é possível prevê-las? - Luciano de Paola; Maria Joana Mäder; Francisco M.B. Germiniani; Patrícia Coral; Jorge A.A. Zavala; Djon J. Watzo; Jorge Kanegusuku; Carlos E.S. Silvado; Lineu C. Werneck (Arquivos de Neuro-Psiquiatria)
The intracarotid sodium amytal test (ISAT or Wada Test) is a commonly performed procedure in the evaluation of patients with clinically refractory epilepsy candidates to epilepsy surgery. Its goal is to promote selective and temporary interruption of hemispheric functioning, seeking to define language lateralization and risk for memory compromise following surgery. Behavioral modification is expected during the procedure. Even though it may last several minutes, in most cases it is subtle and easily manageable. We report a series of patients in whom those reactions were unusually bizarre, including agitation and aggression. Apart of the obvious technical difficulties (patients required physical restraining) those behaviors potentially promote testing delay or abortion and more importantly, inaccurate data. We reviewed those cases, seeking for features that might have predicted their occurrence. Overall, reactions are rare, seen in less than 5% of the ISAT procedures. The barbiturate effect, patients' psychiatric profiles, hemisphere dominance or selectiveness of the injection were not validated as predictors. Thorough explanation, repetition and simulation may be of help in lessening the risk of those reactions. O teste do amital sódico intracarotídeo (TASI ou teste de Wada) é procedimento comum na avaliação de pacientes portadores de epilepsia clinicamente refratária candidatos a cirurgia de epilepsia. Tem por objetivo promover interrupção seletiva e temporária da função hemisferial, definindo lateralização de linguagem e risco de comprometimento de memória no pós-operatório. São esperadas mudanças comportamentais durante o teste, as quais podem durar vários minutos, porém, em geral, são sutis e facilmente manejáveis. Relatamos uma série de casos em que ocorreram comportamentos pouco usuais, bizarros, incluindo agitação e agressividade. Estes comportamentos comprometem o teste (paciente deve ser contido), podendo levar a atrasos ou mesmo abortamento do mesmo, além de produzir dados menos confiáveis. Os casos foram revisados, visando a definição de preditores de sua ocorrência. Estas reações são raras (5% dos casos). Efeito barbitúrico, perfil psiquiátrico, dominância cerebral e seletividade da injeção não puderam ser validados como preditores. Explicações detalhadas, repetição e simulações podem ser utéis na prevenção deste tipo de ocorrência.